Melatonin reverses the enhanced oxidative damage to membrane lipids and improves skin biophysical characteristics in former-smokers – A study in postmenopausal women - Dorota Sagan; Jan Stepniak; Adam Gesing; Andrzej Lewinski; Malgorzata Karbownik-Lewinska (Annals of Agricultural and Environmental Medicine, 2017)
Introduction and objective Protective antioxidative effects of melatonin have been repeatedly documented in experimental and clinical studies. One of the most spectacular exogenous prooxidative agents is cigarette smoking. The aim of the study was to evaluate the level of oxidative damage to membrane lipids (lipid peroxidation; LPO) in blood serum, and in epidermis exfoliated during microdermabrasion collected from former-smokers who were treated with melatonin.